Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/jace.16317
|View full text |Cite
|
Sign up to set email alerts
|

Durable aluminate toughened zirconate composite thermal barrier coating (TBC) materials for high temperature operation

Abstract: Research on advanced thermal barrier coating (TBC) materials capable of operating beyond 1200°C has primarily focused on the rare earth zirconate pyrochlores, particularly gadolinium zirconate (Gd 2 Zr 2 O 7 -GZO). The drawback of this material is a significant reduction in durability due to a low fracture toughness. This study investigates utilization of a thermodynamically compatible gadolinia alumina perovskite (GdAlO 3 -GAP) toughening phase to improve the durability of GZO. Dense pellets were fabricated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Last, this study builds on the results of our previous work suggesting composites of rare earth zirconates and rare earth aluminates as toughened, high temperature phase stable and thermochemically compatible TBCs. 15 The positive results for GAP-CMAS resistance establish that using this material as a toughening agent for GZO will not hamper CMAS resistance in the composite and will in fact likely improve CMAS resistance. Thus, GAP-GZO composites will provide not only toughening,…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Last, this study builds on the results of our previous work suggesting composites of rare earth zirconates and rare earth aluminates as toughened, high temperature phase stable and thermochemically compatible TBCs. 15 The positive results for GAP-CMAS resistance establish that using this material as a toughening agent for GZO will not hamper CMAS resistance in the composite and will in fact likely improve CMAS resistance. Thus, GAP-GZO composites will provide not only toughening,…”
Section: Discussionmentioning
confidence: 92%
“…To combat the low toughness of zirconates, the authors have explored utilizing multiphase composites consisting of GZO modified with a secondary toughening phase in the form of multilayers 10,11 and composites 12–15 . It was demonstrated that minor additions of a toughening phase can have substantial improvement on the erosion durability of coatings while having minimal debit on thermal conductivity for both electron beam‐physical vapor deposition and air plasma spray‐derived coatings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior can be rationalized by the need to have a combination of large, intermediate, and small cation sizes to fill the three distinct sites. Likewise, coatings based on or containing rare earth aluminates are likely to cause a shift in reaction equilibria toward garnet formation 33 . Garnet is observed less frequently as an equilibrium reaction product at higher temperatures, and in some cases has been observed to grow on cooling rather than at temperature 26,29,34 …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, coatings based on or containing rare earth aluminates are likely to cause a shift in reaction equilibria toward garnet formation. 33 Garnet is observed less frequently as an equilibrium reaction product at higher temperatures, and in some cases has been observed to grow on cooling rather than at temperature. 26,29,34 Initial insight into the relative stability of apatite and garnet is gained by examining the endmembers RE 9.33 (SiO 4 ) 6 O (the apatite terminus in the REO 1.5 -SiO 2 binary), Ca 2 RE 8 (SiO 4 ) 6 O 2 (the vacancy-free nominal apatite stoichiometry), and RE 3 Al 5 O 12 (the rare earth aluminate garnet, RE-AG).…”
Section: Introductionmentioning
confidence: 99%